Besökarpåverkan hos lodjur (Lynx lynx) på djurpark - Lindau, Blenda (SLU/Dept. of Animal Environment and Health (until 231231), 2022)
Zoo visitors can affect captive animals in a negative, neutral or positive way. To achieve great welfare for the animals we need a better understanding of how visitors influence their behaviours. The Eurasian lynx (Lynx lynx) is not as studied as other Felidae and there is a lack of knowledge on how to manage stereotypies, such as pacing. This study analysed the behaviours of three captive lynx: a mother and her two one year old cubs, regarding visitor effect. Their enclosure was divided into three zones and the behaviours categorised into active and inactive behaviours. The study monitored the lynxes over nine days with a focal observation on all three animals simultaneously, and the behaviours were registered with instantaneous sampling each minute during a total of 268 minutes. The lynxes spent most of their time laying down, walking and sleeping, and the mother spent a quarter of her time pacing. The results also indicate no difference in active or inactive behaviours regarding visitor numbers. They spent most of their time in the zone furthest away from visitors, but also more time in the zone closest to visitors when there were many people around the enclosure. The lynxes were also more visible with many visitors in sight. Their choosing for what zone to be in is most likely related to preference and what resources, like resting places, that exist there. There also seemed to be individual differences in how the animals were affected by visitors, since one of the cubs tended to stay further in the enclosure. Regarding the stereotypies, further research is needed to determine how to help lynxes and other Felidae to improve their welfare in a captive environment.